Peran Orang Tua dalam Pembiasaan Hidup Bersih dan Sehat pada Anak - MM Shodiq, Nurul Aini; Mokodongan, Balgis Nur Fadhillah; Juniarti, Yenti; Laiya, Sri Wahyuningsi (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
The objective of this research was to figure out the Role of Parents in Habituation of Clean and Healthy Living Behavior in Children of Group A at TK (Kingdergarten) Kihadjar Dewantoro 1, Kota Timur Subdistrict, Gorontalo City. It employed a qualitative descriptive method with the data collection techniques were observation, interviews, and documentation. In the meantime, the data analysis technique in this research was an interactive model, according to Milles and Huberman. The research finding could be observed optimally based on four indicators on the role of parents, namely (1) the role of parents as educators where parents provide guidance of clean and healthy living behabior for children. (2) The role of parents as motivators in which parents motivate children to have a clean and healthy living behavior. (3) The role of parents as the role model where parents provide examples to children in terms of clean and healthy living behavior. (4) The role of parents as facilitators is where parents provide facilities and infrastructure to support healthy living for children.